Electronic Spectra and High-Resolution B-type Delayed Fluorescence of Salicylidene-m-bromo-aniline in Hexane - KÜÇÜK, HALUK (TAYLOR & FRANCIS INC, 2009)
The observation of triplet--triplet absorption and emissions of salicylidene-m-bromo-aniline is complicated by possible colored isomer formation during the optical pumping. The short-lived (singlet--singlet) and long-lived (triplet--triplet) absorption spectra were recorded photographically by microsecond flash and nanosecond laser flash photolysis techniques. Salicylidene--aniline complexes were purified by repeated recrystallization until further recrystallization produced no further changes for X-ray diffraction pattern and optical absorption emission properties. B-type delayed fluorescence, T-T absorption, color isomer absorption, and T-T emissions of this compound were recorded for the first time.
Keywords: activation energy; B-type delayed fluorescence; entropy change; salicylidene-m-bromo-aniline; T-T absorption; T-T fluorescence; T-T ABSORPTION; TRIPLET-STATE PROPERTIES; PHOTOCHROMISM; PHOTOLYSIS; BENZENE; SA